Four‐State Electrochromism in Tris(4‐aminophenyl)amine‐ terephthalaldehyde‐based Covalent Organic Framework - Kumar Silori, Gaurav; Chien, Szu‐Chia; Lin, Li‐Chiang; Ho, Kuo‐Chuan (Angewandte Chemie International Edition, 2025)
Covalent organic frameworks (COFs) are of massive interest due to their potential application spanning diverse fields such as gas storage and separation, catalysis, drug delivery systems, sensing, and organic electronics. In view of their application‐oriented quest, the field of electrochromism marked a significant stride with the reporting of the first electrochromic COF in 2019 [J. Am. Chem. Soc. 2019, 141, 19831–19838]. Since then, new and novel COF structures with electrochromic features (denoted as ecCOFs) have been searched continuously. Yet, only a handful of ecCOFs have been constructed to date. A closer look at these reports suggests that multielectrochromism (showing at least three redox color states) in a COF assembly has only been achieved once, manifested through three‐state electrochromism [Angew. Chem. 2021, 133, 12606–1261]. Herein, we report four‐state electrochromism in tris(4‐aminophenyl)amine‐terephthalaldehyde (TAPA‐PDA)‐based COF constructed through the metal‐catalyst free Schiff base approach. The four‐state (orange, pear, green, and cyan) electrochromism demonstrated by the TAPA‐PDA ecCOF opens several futuristic avenues for ecCOF′s end use in flip‐flop logic gates, intelligent windows, decorative displays, and energy‐saving devices. While several electrochromic COFs (denoted as ecCOFs) have been reported to date, a closer survey suggests that multielectrochromism (showing at least three redox color states) in a COF assembly has only been achieved once, manifested through three‐state electrochromism [Angew. Chem. 2021, 133, 12606–1261]. Herein, we report four‐state (orange, pear, green, and cyan) electrochromism in tris(4‐aminophenyl)amine‐terephthalaldehyde‐based COF constructed through the metal‐catalyst free Schiff base approach.